Trio Album for violin, violoncello & piano, vol. IV Violoncello part - ARENSKY, A (The Boston Music Co.)
ElegienAdagionSlavic dancenMelody in DnSerenadenGavottenSpanish dancenThe RosarynMoorish nightsongnAndante religioso